Indonesia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2010)
This paper takes an in-depth look into recent trade patterns to assess the extent of such concerns. It is found that (i) there is no strong evidence of Dutch Disease; (ii) weak performance in some sectors, so far, does not appear to be linked to the commodity boom; and (iii) although further reliance on commodities has increased Indonesia's vulnerability to export price volatility, the terms of trade have actually been rather stable as import and export prices co-move markedly, mitigating such vulnerability.